Diabetes – what type? - Otto-Buczkowska, Ewa (Przewodnik Lekarza/Guide for GPs, 2012)
The diagnosis of diabetes subtypes is usually based on criterions as the age at onset, phenotype and biochemical diagnostic criteria. The focus is predominantly on diagnosing type 1 and type 2 diabetes. Maturity-onset diabetes of the young (MODY) is often misdiagnosed as type 1 or type 2 diabetes. It usually develops in childhood, adolescence or young adulthood. Latent autoimmune diabetes in adults (LADA) is a form autoimmune-mediated diabetes in adults. The progressinon beta-cell failure is slower than in classic type 1 diabetes. Patients are often misdiagnosed as type 2 diabetes.